2017
DOI: 10.4049/jimmunol.1700141
|View full text |Cite
|
Sign up to set email alerts
|

T Follicular Helper Cell–Derived IL-4 Is Required for IgE Production during Intestinal Helminth Infection

Abstract: IgE production plays a crucial role in protective as well as pathogenic type 2 immune responses. Although the cytokine IL-4 is required for the development of IgE-producing plasma cells, the source of IL-4 and cellular requirements for optimal IgE responses remain unclear. Recent evidence suggests that T follicular helper (Tfh) cells are the primary producer of IL-4 in the reactive lymph node during type 2 immune responses. As Tfh cells are also required for the development of plasmablasts derived from germina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 43 publications
(75 reference statements)
3
59
0
Order By: Relevance
“…However, Tfh17 and Tfh2 cells are yet to be described in murine systems. There are, however, a plethora of reports regarding IL-4-producing Tfh cells in the context of B cell activation, IgE class switching, anti-helminth immunity, and asthma, and these cells could be considered murine versions of Tfh2 cells (Kobayashi et al, 2016;Meli et al, 2017;Reinhardt et al, 2009;Weinstein et al, 2016;Yusuf et al, 2010). Nevertheless, in contrast to human Tfh2 cells, the IL-4 + Tfh cells examined in these reports do not express GATA-3.…”
Section: Discussionmentioning
confidence: 91%
“…However, Tfh17 and Tfh2 cells are yet to be described in murine systems. There are, however, a plethora of reports regarding IL-4-producing Tfh cells in the context of B cell activation, IgE class switching, anti-helminth immunity, and asthma, and these cells could be considered murine versions of Tfh2 cells (Kobayashi et al, 2016;Meli et al, 2017;Reinhardt et al, 2009;Weinstein et al, 2016;Yusuf et al, 2010). Nevertheless, in contrast to human Tfh2 cells, the IL-4 + Tfh cells examined in these reports do not express GATA-3.…”
Section: Discussionmentioning
confidence: 91%
“…Recent experiments using mice with conditional loss of Bcl6 or IL‐6 receptor signaling in T cells, which abrogates Tfh cell development, showed that Tfh cells are critical for inducing IgE in multiple type 2 responses including to allergens . Further, bone marrow chimera experiments that isolated IL‐4 deficiency to Tfh cells also demonstrated severely reduced IgE responses, suggesting that Tfh cell‐derived IL‐4 is the main driver of IgE in vivo . Supporting these findings of the importance of Tfh cells in directing IgE responses, a functional dichotomy between Th2 and Tfh cells in regulating peripheral inflammation and IgE, respectively, has begun to emerge.…”
Section: Tfh Cells As Drivers Of Ige Responsesmentioning
confidence: 86%
“…Based on the recent evidence, the model that emerges for IgE induction is that IL‐4‐producing Tfh cells drive IgE responses . However, allergens typically induce high‐affinity anaphylactic IgE responses, which are rarely induced during helminth infections as previously discussed.…”
Section: Nature Of Tfh Cells That Drive Ige Response To Helminths Andmentioning
confidence: 99%
“…Through the secretion of IL‐4 and IL‐13, Th2 cells promote allergen‐specific IgE production by B cells . Although Th2 cells have historically been considered the primary mediators of allergic sensitization, there is growing evidence that T follicular helper (Tfh) cells also play a critical role in promoting IgE production . Through their ability to provide help to germinal centre B cells, Tfh cells promote antibody isotype class switching and B cell differentiation into plasma and memory cells .…”
Section: Introductionmentioning
confidence: 99%
“…25 Although Th2 cells have historically been considered the primary mediators of allergic sensitization, there is growing evidence that T follicular helper (Tfh) cells also play a critical role in promoting IgE production. 15,[26][27][28] Through their ability to provide help to germinal centre B cells, Tfh cells promote antibody isotype class switching and B cell differentiation into plasma and memory cells. 29 Accordingly, recent studies have shown that Tfh cells are essential for the development of IgE responses against inhaled antigens.…”
Section: Introductionmentioning
confidence: 99%